2010
DOI: 10.1002/cphc.201000596
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the Photochemistry of Bipyridylic Compounds by Symmetric Substitutions

Abstract: A quantum electronic study of the effect of substituents on (2,2'-bipyridyl)-3,3'-diol and (2,2'-bipyridyl)-3,3'-diamine is presented. A large difference in the photochemical behavior between the original and the substituted selected systems is expected. For the sake of simplicity, the study is restricted to the symmetrically bi-substituted compounds: fluorine, the more electronegative atom and thus a strong σ-acceptor but also a weak π-donor group, and NO(2), a strong π-acceptor substituent. Among the large s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 60 publications
(77 reference statements)
0
5
0
Order By: Relevance
“…Because of the large size of the p conjugated system in BSP, a systematic CASSCF study would need a far too large active space requiring an unattainable amount of computational resources. Very recently 45,46 the same strategy has been successfully used to analyze a series of bipyridyl derivatives.…”
Section: Theoretical Resultsmentioning
confidence: 99%
“…Because of the large size of the p conjugated system in BSP, a systematic CASSCF study would need a far too large active space requiring an unattainable amount of computational resources. Very recently 45,46 the same strategy has been successfully used to analyze a series of bipyridyl derivatives.…”
Section: Theoretical Resultsmentioning
confidence: 99%
“…Recent quantum modelings were done for SA and they showed that ESIPT occurs from a planar enol* which gives a planar cis-keto*. This planar cis-keto* is not stable and undergos out-of-plane torsion which is the precursor of cis−trans isomerization to the trans-keto photoproduct . Thus one hypothesis for the two fluorescent cis-keto* is a planar and a nonplanar isomer or different nonplanar isomers.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, the family of aromatic Schiff bases is to be highlighted because the photochromism in these compounds is produced through an ESIPT process. [22,23] Recently, interest in photochromic systems has suddenly increased because of the intriguing possibility of using them as molecular optical switches or photomemory devices. The use of organic molecules for the future realization of digital processors and storage media at the miniaturized level is at present a hot topic in applied science.…”
Section: Introductionmentioning
confidence: 99%